Risk assessment of chronic toxicity for exposure to cadmium in rats (Rattus norvegicus) - García, Mesías M. (2014)
Cadmium beacause its widespread use at industrial level can enter to food chain and cause bioaccumulation in different feed systems and in the human body. The objective was to assess the risk of chronic toxicity, characterizing potential teratogenic effects and clinical signs of toxicity in albino rats (Rattus norvegicus) of the Holtzman strain. To Guides experimental design of the Organization for Economic Cooperation and Development (OECD) were adapted. Two levels of cadmium nitrate intakes were tested: 40 and 80 μg Cd/day, administered with drinking water for 120 days; with the respective control group. Mothers rats, during pregnancy, and their offspring, from birth to 120 days, were observed in their behaviors The pups were differenced by birth weight (control group: 7,22 ± 1,1; 40 μg Cd/day group: 5,86 ± 0,45; and 80 μg Cd/day group: 5,30 ± 0,46 g), by body size, skin color with bleeding signs. The embryo sac at 18 days of gestation, showed differences in color, this was pink in the control group and ranged red wine in groups exposed to daily intakes of cadmium trials. In pups achondroplasia was manifested during the experimental period. Was concluded that cadmium produces teratogenic and toxic effects with structural and functional damage in liver, uterus and annex and vascularization in adult albino rats exposed to chronic intake of the mineral.